COVER PAGETHE SYMBOLISM OF KOLANUT IN IGBO COSMOLOGY: A RE-EXAMINATION - Chukwudi G. Chidume (European Scientific Journal, ESJ, 2014)
This paper considers the symbolism of kolanut according to Igbo worldview. How kolanut helps to shape the people‘s philosophical ideology especially, in relation to religion. The roles of kolanut within the Igbo socio-cultural context and the values attached to these roles will be examined. The roles of kolanut as a means of socialization, education and transmission of cultural values from the preceding to succeeding generations will come under consideration. Equally, this paper looks at the traditional rules regarding not only the uses but more essentially the mode of kolanut presentation, blessing, breaking and sharing of kolanut. How these rules and kolanut have persisted in the face of social and cultural changes which have affected the Igbo people shall be reviewed. The roles played by kolanut in Igbo religion will come under study, this is to correct some of the misconceptions by writers who are motivated by Eurocentric idealism but quite oblivious of the Igbo cultural setting and the place of kolanut in it. The onslaught of Western civilization causing the change of attitude among the young generation towards kolanut as a vital aspect of our culture tends to pose a threat to the future and survival of kolanut. Again, the study of Igbo culture as many have done, rarely gives an indepth knowledge on the concept, roles and symbolism of kolanut as one of the sacred objects like Ofo and Shrines in Igboland. Most times it is forgotten that without kolanut, shrines cannot be attended to. Many people think that the spiritual significance and sacramental symbolism are not worth exploring. They therefore refuse to try and discover the ritual ramifications, claiming that to probe into the mystery demystifies the matter. Kolanut symbolism is not mysteriously inexplicable. It is a revered symbol of social intercourse with deep social relevance.